Palatal Re-Repair With Double-Opposing Z-Plasty in Treatment of Velopharyngeal Insufficiency of Patients With Unilateral Cleft Lip and Palate. Issue 8 (November 2020) - Ahti, Veera; Alaluusua, Suvi; Rautio, Jorma; Saarikko, Anne
Abstract : Background: Velopharyngeal insufficiency (VPI) is a common problem after cleft palate repair that is often related to palatal shortening and insufficient levator reconstruction. For VPI correction in our cleft center, palatal re-repair with double-opposing Z-plasty is the standard operation. Aims: To assess the efficacy of double-opposing Z-plasty in treatment of VPI after primary surgery for unilateral cleft lip and palate (UCLP). Methods: This retrospective analysis comprised 109 consecutive UCLP patients born between 1997 and 2014 with VPI that required re-operation, and were operated on by 2 highvolume cleft surgeons, followed by perceptual and instrumental (Nasometer) evaluation of velopharyngeal competence (VPC). Results: Preoperatively, VPI was severe in 96% (105 of 109) and mild-to-moderate in 4% (4 of 109). Median age at surgery was 5.6 years (range 2.8–21.9). Postoperatively, 84% of patients achieved adequate VPC: 65% (71 of 109) were competent and 19% (21 of 109) borderline competent. Postoperative adequate VPC was 89% (70 of 79) in nonsyndromic Finnish patients, 50% (4 of 8) in syndromic patients, and 82% (18 of 22) in adoption children. Compared to Finnish nonsyndromic patients, patients with syndrome had more residual VPI ( P  = 0.003), but no statistically significant difference existed for adoption patients ( P  = 0.251). Complications of the double-opposing Z-plasty included hemorrhage, postoperative mild airway obstruction, and wound-healing problems, each arising in 2 (1.8%) patients. Fourteen (13%) patients needed a second VPI operation. Conclusion: Double-opposing Z-plasty seems to be a good and safe treatment option for VPI in patients with previously repaired UCLP with a success rate of 84%. Abstract : Supplemental Digital Content is available in the text